Plasma proteins in children with trichuris dysentery syndrome. Issue 3 (March 1997) - Cooper, E S; Ramdath, D D; Whyte-Alleng, C; Howell, S; Serjeant, B E
Abstract : AIMS: To determine whether in Trichuris trichiura dysentery there is (1) evidence of a systemic inflammatory response, (2) evidence that the plasma protein disturbance has special characteristics compared with uninfected children in the endemic environment. METHODS: Three groups of children (age 1.6 to 11.4 years) were studied: 53 cases of trichuris dysentery syndrome (TDS), 16 cases of chronic non-secretory diarrhoea not infected with the parasite ("disease controls", DC), and 20 asymptomatic, parasite-free primary schoolchildren (normal controls, NC). C reactive protein, alpha 1 antitrypsin, caeruloplasmin, albumin, total globulin, fibrinogen, fibronectin, ferritin, and transferrin were measured on a single occasion for each. The study was thus a cross sectional descriptive survey for group comparison. Plasma viscosity was measured on admission for TDS and DC and repeated after six weeks and six months for TDS. RESULTS: Plasma C reactive protein, alpha 1 antitrypsin, total globulin, fibronectin, and viscosity were significantly higher in TDS than in NC. DC children also had acute phase protein elevations (C reactive protein, caeruloplasmin, viscosity). However, the increase in caeruloplasmin was specific to the DC group while an increase in fibronectin was specific to the TDS group. Serial measurement of viscosity in TDS showed a modest but significant fall during the six months following treatment. CONCLUSIONS: There is an acute phase response in intense trichuriasis and a specific elevation of plasma fibronectin. Plasma viscosity remains abnormally high six months after treatment, although lower than at diagnosis.